PFAS residue analysis in fish and fish feed by applying a modified QuEChERS method in combination with LC-HRMS detection - Ourania Koloka; Vasiliki Boti; Dimitra Hela; Triantafyllos Albanis; Ioannis Konstantinou (Emerging Contaminants, 2025)
A targeted method for the quantitative determination of PFAS residues in fish feed and marine aquaculture fish species was developed and validated in the current study. This method combines a modified QuEChERS extraction methodology that includes sonication followed by Liquid Chromatography- Linear Ion Trap/Orbitrap High Resolution Mass Spectrometry (LC- LTQ/Orbitrap HRMS) analysis. The original QuEChERS method was selected with some modifications and the clean-up step was performed using Enhanced Matrix Removal-Lipid (EMR-Lipid) as the dispersive solid-phase extraction (dSPE) agent. The optimization of the sample preparation included different sorbents in the clean-up step for the fish feed matrix, and various sample amounts and sonication treatment times were tested for both matrices. The optimized modified extraction procedure for the analysis of PFAS residues in fish feed was fully validated exhibiting recoveries between 51.1 % and 101.2 %, relative standard deviations (RSDs) < 20.7 % and LOQs between 0.03 ng/g and 0.50 ng/g. Furthermore, the current study provides validation data for the analysis of PFAS residues in fish tissues according to the analytical method proposed for PFAS analysis in fish feed, with linearity values ≥ 0.9901, recoveries ranging from 55.5 to 113.3 % and precision values < 20.0 % (%RSD). Matrix effect studies demonstrated low, and medium values and the method showed an acceptable expanded uncertainty of <57.66 %. Finally, the modified method was applied to analyze fish and fish feed samples from Greek aquaculture facilities. No PFAS residues were detected in any of the fish samples, whereas two fish feeds contained PFOS residues and one contained the target PFOA.